2010
DOI: 10.1021/la100635r
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Adsorption of Volatile Organic Compounds in a Large-Pore Metal−Organic Framework, IRMOF-1

Abstract: Metal-organic frameworks have been proposed as useful sorbents for the capture of a variety of compounds. In this work, inverse gas chromatography (IGC) utilizing micropacked capillary columns was used to probe the adsorption of more than 30 volatile organic compounds (VOCs) on IRMOF-1. In an attempt to study the effect of structural degradation upon VOC adsorption, multiple samples of IRMOF-1 with widely ranging properties were investigated. Trends in the differential enthalpies and equilibrium constants for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 61 publications
(95 reference statements)
10
87
5
Order By: Relevance
“…The current adsorbents used to remove VOCs, such as carbonaceous adsorbents, zeolites, silicates, and polymeric resins, are limited by problems related to rigorous regeneration conditions, slow kinetics, low surface areas, and unacceptable stability. 28 Metal-organic framework materials have been proposed to remove VOCs, though compared to small molecules, such as H 2 , CH 4 , and CO 2 , only a limited number of studies reported about the adsorption of larger organic molecules in MOFs. A systematic study has been done by Luebbers et al 28 on the use of IRMOF-1 to adsorb a variety of VOCs, mainly alkanes, alkylbenzenes, and some common organic solvents.…”
Section: Inorganic Toxic Gas Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…The current adsorbents used to remove VOCs, such as carbonaceous adsorbents, zeolites, silicates, and polymeric resins, are limited by problems related to rigorous regeneration conditions, slow kinetics, low surface areas, and unacceptable stability. 28 Metal-organic framework materials have been proposed to remove VOCs, though compared to small molecules, such as H 2 , CH 4 , and CO 2 , only a limited number of studies reported about the adsorption of larger organic molecules in MOFs. A systematic study has been done by Luebbers et al 28 on the use of IRMOF-1 to adsorb a variety of VOCs, mainly alkanes, alkylbenzenes, and some common organic solvents.…”
Section: Inorganic Toxic Gas Removalmentioning
confidence: 99%
“…28 Metal-organic framework materials have been proposed to remove VOCs, though compared to small molecules, such as H 2 , CH 4 , and CO 2 , only a limited number of studies reported about the adsorption of larger organic molecules in MOFs. A systematic study has been done by Luebbers et al 28 on the use of IRMOF-1 to adsorb a variety of VOCs, mainly alkanes, alkylbenzenes, and some common organic solvents. It was noted that the adsorption enthalpies vary linearly with the increase in chain length for a series of n-alkanes and alkylbenzenes.…”
Section: Inorganic Toxic Gas Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of recent environmental concerns, much of the focus for guest incorporation within porous materials has centered on the storage of possible alternative fuels such as CH 4 and H 2 , 1-6 pollution-control reservoirs for CO 2 , [7][8][9] storage of dangerous waste products like volatile organic compounds [10][11][12] and radioactive waste, [13][14][15][16] or water adsorption for sanitation measures. [17][18][19] Initial assessment of the suitability of potential new materials for such encapsulation applications can reasonably focus on the analysis of void space within their crystalline solidstate frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…[4] To date, several investigations of MOF-based chromatography have been published, mainly addressing HPLC and packed-column applications. [5][6][7] However, capillary-based gas chromatography has only been addressed by the work of Gu and Yan, who deposited MIL-101 and ZIF-8 onto fusedsilica columns by evaporating the solvent from suspensions of MOFs, with which they separated xylene isomers and linear alkanes. [8,9] Of all of the established chromatographic capillaries, socalled PLOT columns (porous layer open tubular) coated with materials such as porous alumina or polystyrene, typically possessing pore sizes in the range of macro-and mesopores, come closest to the concept of an MOF-coated capillary, although their pore sizes are significantly larger than those of MOFs.…”
Section: Introductionmentioning
confidence: 99%